From the outbreak to the class struggle. Keys for the analysis of the results of the plebiscite for a new constitution in Chile - Arancibia-Bustos, Álvaro (2021)
The objective of this article is to investigate the relationship between class position and vote in the plebiscite for a new constitution in Chile. For the above, the voting results were taken and statistically associated with class positions. The results show a high positive correlation between the Approve option, the Constitutional Convention option, and the proletariat; meanwhile, this relationship is reversed, with a high negative force, in the case of the bourgeoisie and managerial experts. These results suggest a polarization in the defense of class interests, based on the possibility of modifying the status quo enshrined in the current constitution.